2019
DOI: 10.5751/ace-01422-140209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of off-highway vehicles on avian abundance and diversity in a designated vehicular recreation area

Abstract: Off-Highway Motor Vehicle Recreation Division, Hollister Hills -State Vehicular Recreation Area ABSTRACT. More people are engaging in recreation on public lands in the United States than ever before. However, increased recreation can be detrimental to wildlife species. Managers need to understand how recreational activities, such as driving motor vehicles through natural areas, can affect a range of species so that they can balance access to nature with preservation of wildlife communities. We assessed the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…ORV activity was found to reduce total shorebird abundance (Tarr et al, 2010) but only reduced the abundance of 2 of 18 species of breeding songbirds (Barton and Holmes, 2007). Further, a study at a recreational area in California found non-negative effects on community-level bird abundance and no discernable effect on diversity in both the winter and spring (Cole et al, 2019), suggesting that effects of ORV use on bird communities may vary depending upon the habitat, driver behavior (e.g., speed, direction, etc. ), or species-specific responses.…”
Section: Impacts On Vertebrates Birdsmentioning
confidence: 96%
See 1 more Smart Citation
“…ORV activity was found to reduce total shorebird abundance (Tarr et al, 2010) but only reduced the abundance of 2 of 18 species of breeding songbirds (Barton and Holmes, 2007). Further, a study at a recreational area in California found non-negative effects on community-level bird abundance and no discernable effect on diversity in both the winter and spring (Cole et al, 2019), suggesting that effects of ORV use on bird communities may vary depending upon the habitat, driver behavior (e.g., speed, direction, etc. ), or species-specific responses.…”
Section: Impacts On Vertebrates Birdsmentioning
confidence: 96%
“…Treatments for experimental studies (n = 10) involved driving four-wheel drive vehicles (n = 8), ATVs (n = 2), and/or motorcycles (n = 4) a specified number of times over the experimental area. (Assaeed et al, 2019); (D) ORV trail in Douglas-fir forest in the interior of British Columbia, Canada (Photo by: Laura Ploughe) (E) ORV trail in a chapparal in California, USA (Cole et al, 2019).…”
Section: Soilsmentioning
confidence: 99%